Inpatient cardiac monitoring using a patch‐based mobile cardiac telemetry system during the COVID‐19 pandemic. (4th September 2020) - Braunstein, Eric D.; Reynbakh, Olga; Krumerman, Andrew; Di Biase, Luigi; Ferrick, Kevin J.
Abstract: Introduction: Coronavirus disease 2019 (COVID‐19) is a worldwide pandemic, and cardiovascular complications and arrhythmias in these patients are common. Cardiac monitoring is recommended for at risk patients; however, the availability of telemetry capable hospital beds is limited. We sought to evaluate a patch‐based mobile telemetry system for inpatient cardiac monitoring during the pandemic. Methods: A prospective cohort study was performed of inpatients hospitalized during the pandemic who had mobile telemetry devices placed; patients were studied up until the time of discharge or death. The primary outcome was a composite of management changes based on data obtained from the system and detection of new arrhythmias. Other clinical outcomes and performance characteristics of the mobile telemetry system were studied. Results: Eighty‐two patients underwent mobile telemetry device placement, of which 31 (37.8%) met the primary outcome, which consisted of 24 (29.3%) with new arrhythmias detected and 18 (22.2%) with management changes. Twenty‐one patients (25.6%) died during the study, but none from primary arrhythmias. In analyses, age and heart failure were associated with the primary outcome. Monitoring occurred for an average of 5.3 ± 3.4 days, with 432 total patient‐days of monitoring performed; of these, QT‐interval measurements were feasible in 400 (92.6%). Conclusion: A mobile telemetry system was successfully implemented for inpatient use during the COVID‐19 pandemic and was shown to be useful to inform patient management, detect occult arrhythmias, and monitor the QT‐interval. Patients with advanced age and structural heart disease may be more likely to benefit from this system.